Roles of Dental Mesenchymal Stem Cells in the Management of Immature Necrotic Permanent Teeth - Cui, Dixin; Yu, Sihan; Zhou, Xin; Liu, Ying; Gan, Lu; Pan, Yue; Zheng, Liwei; Wan, Mian (Frontiers in Cell and Developmental Biology, 2021)
Dental caries and trauma always lead to pulp necrosis and subsequent root development arrest of young permanent teeth. The traditional treatment, apexification, with absence of further root formation, results in abnormal root morphology and compromises long-term prognosis. Regeneration endodontics procedures (REPs) have been developed and considered as an alternative strategy for management of immature permanent teeth with pulpal necrosis, including cell-free REPs and cell-based REPs. Cell-free REPs, including revascularization and cell homing with molecules recruiting endogenous mesenchymal stem cells (MSCs), have been widely applied in clinical treatment, showing optimistic periapical lesion healing and continued root development. However, regenerated pulp-dentin complex is still absent in these cases. Dental MSCs, as one of the essentials of tissue engineering, are vital seed cells in regenerative medicine. Dental MSC-based REPs have presented promising potential with pulp-dentin regeneration in large animal studies and clinical trials via cell transplantation. In the present review, we summarize current understanding of the biological basis of clinical treatments for immature necrotic permanent teeth, the roles of dental MSCs during this process, and update the progress of MSC-based REPs in the administration of immature necrotic permanent teeth.